TINGKAT PENGETAHUAN IBU BALITA TENTANG PENYAKIT ISPA BERADSARKAN UMUR DAN PENDIDIKAN DI DESA BALAPULANG WETAN KEC. BALAPULANG KAB. TEGAL TAHUN 2008 - Ririn Indrawati (Viva Medika, 2008)
The purpose of this research is to determine the level of knowledge of mothers ofrespiratory disease by age and education in the village Balapulang BalapulangWetan District of Tegal 2008.This research method is a descriptive study with cross sectional approach.Population and sample in this study were mothers who have children aged 0-5years in Desa Wetan Balapulang Balapulang District of Tegal. Total sample is 55respondents drawn using Proportional Stratified Random Sampling technique.Instrument in this study was a questionnaire.The results of this study are mostly less knowledgeable respondents as many as 23people (41.8%), aged 20-35 years as many as 31 people (56.35%), with asecondary school education level, there are 26 (47.3%). While the level ofknowledge of mothers by the age of majority aged 20-35 years with sufficientknowledge as much as 14 respondents (45.2%) and the mother's level ofknowledge based education mostly junior high school education with lessknowledge of as many as 15 people (57.7%).The conclusion in this study that the level of knowledge of mothers about ARIberadsarkan age and education level are sufficient in the age group 20-35 yearsand less in secondary school education. Keywords: knowledge of respiratory disease, the toddler's mother.